The aim remains: Monetary union - Alwin Münchmeyer (Intereconomics, 1971)
No doubt the monetary measures taken by the Government of the Federal Republic on May 10 have caused quite a stir. The question is: Can the European economic and monetary union still be achieved, in spite of the German measures?
Keywords: 330